2015
DOI: 10.4049/jimmunol.1302689
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism of Ptpn22 Is Associated with Type 1 Diabetes in the BioBreeding Rat

Abstract: The R620W variant of PTPN22 is one of the major genetic risk factors for several autoimmune disorders including type 1 diabetes (T1D) in humans. In the BioBreeding T1D-prone (BBDP) rat, a single nucleotide polymorphism in Ptpn22 results in an A629T substitution immediately C-terminal to the aliphatic residues central to the Ptpn22–C-terminal Src kinase interaction. This variant exhibits a 50% decrease in C-terminal Src kinase binding affinity and contributes to T cell hyperresponsiveness. Examination of BBDP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The ileal and cecal communities of DR+/+ ND and F+/+ ND rats were most similar, yet the peripheral inflammatory state was higher in DR+/+ rats, as measured by plasma cytokine levels (IL-1a, IL-4, IL-13, IL-18) and plasma induced transcription analysis. This result is consistent with the BB rat lineage possessing genetic variation that influences immune responsiveness and possibly increased intestinal permeability [ 86 , 87 ] as is suggested by the measurement of higher HMGB1-independent plasma TLR4 reporter activity in DR+/+ rats. Previously, we reported that the susceptibility of DR+/+ rats to KRV triggered diabetes declines with age and is coincident with the temporal acquisition of an IL-10- and TGF-β-mediated immunoregulated state [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…The ileal and cecal communities of DR+/+ ND and F+/+ ND rats were most similar, yet the peripheral inflammatory state was higher in DR+/+ rats, as measured by plasma cytokine levels (IL-1a, IL-4, IL-13, IL-18) and plasma induced transcription analysis. This result is consistent with the BB rat lineage possessing genetic variation that influences immune responsiveness and possibly increased intestinal permeability [ 86 , 87 ] as is suggested by the measurement of higher HMGB1-independent plasma TLR4 reporter activity in DR+/+ rats. Previously, we reported that the susceptibility of DR+/+ rats to KRV triggered diabetes declines with age and is coincident with the temporal acquisition of an IL-10- and TGF-β-mediated immunoregulated state [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the existence of additional genetic modifiers of immune function is the recent report that BB rats possess a single nucleotide substitution in the protein tyrosine phosphatase non-receptor type 22 (PTPN22) gene (a gene also associated with human T1D susceptibility) that results in T-cell hyper-responsiveness (75). Another source of inflammation could be intestinal hyper-permeability, possibly mediated by genetic variation and/or the composition of the intestinal microbiome, which could promote translocation of bacteria and/or PRR ligands and a heightened systemic innate inflammatory state.…”
Section: Evidence Of An Underlying Innate Inflammatory State Associatmentioning
confidence: 81%
“…Fig 6 lists 19 networks of the interactions among three or more genes on individual chromosomes. For instance, the interactions among genes MAGI3 (rs1230658), PHTF1(rs1936398) and PTPN22 (rs1217410) on Chr 1 are evident, which is associated with Type 1 diabetes [ 41 , 42 ]. Part of ZRANB3 gene (213 bp; rs6742030) on Chr 2 is antisense to spliced RAB3GAP1 gene (rs7422031; d = -0.0483±0.0075; r 2 d<0 = 0.6047±0.5590) according to the information from http://www.ncbi.nlm.nih.gov/IEB/Research/Acembly/ .…”
Section: Resultsmentioning
confidence: 99%